Focused physicochemical stability study of reconstituted trastuzumab biosimilar SB3 (Ontruzant®) stored in the original vials over 28 days - Knoll Laura; Thiesen Judith; Krämer Irene (De Gruyter, 2024)
Trastuzumab biosimilar SB3 (Ontruzant®), a HER2 binding monoclonal antibody, is available as powder for concentrate for solution for infusion. According to the summary of product characteristics, the reconstituted solution (21 mg/mL) is physicochemically stable for 7 days when stored refrigerated at 2-8 °C. The objective of this focused study was to determine the extended physicochemical stability of trastuzumab SB3 reconstituted with water for injection and stored in the original glass vials under refrigeration or at room temperature over a period of 28 days.